Severe metabolic alkalosis: a case report. Issue 6298 (17th October 1981) - Javaheri, S; Nardell, E A
Abstract : A 45-year-old man who was admitted with nausea, vomiting, and abdominal pain was found to have severe metabolic alkalosis, with a PaCO2 of 11.4kPa (85.5 mm Hg), PaO2 of 5.8 kPa (43.5 mm Hg), pH of 7.61, and plasma bicarbonate concentration of 82.0 mmol/l. He was treated with oxygen, intravenous physiological saline, and phenytoin and improved within 48 hours. Radiographs showed gastric outlet obstruction secondary to peptic ulcer, which was treated by surgery. Though sever, the rise in carbon dioxide concentration in this patient was probably lifesaving. The PaCO2 was therefore allowed to fall gradually as the alkalosis was treated. The return of both PaCO2 and plasma bicarbonate values to normal in parallel suggests that hypoventilation compensated for the metabolic alkalosis and emphasises the importance of conservative treatment in cases of metabolic alkalosis.